Pendampingan dan Pelatihan Upgrading Packaging dalam Pembuatan Jamu KWT Al-Ittihad di Motong Irok, Desa Darmaji, Kecamatan Kopang, Kabupaten Lombok Tengah, NTB - Baiq Maoni Yarni; Era Pazira; Baiq Fina Lestari; Nuranita Nuranita; Oktavia Harti Ningsih; Sarina Khairunnisa; Sendi Nur Aulia; Muhammad Amar Hikmalloh; Sahril Sabirin; Aan Sopian; Ananda Nur Hidayah; I Wayan Sudiarta (Jurnal Gema Ngabdi, 2022)
Traditional herbs are natural or herbal medicines that have been used for a long time and have been proven to be good for health, because they do not contain chemicals. Indonesia has a diversity of ethnobotany (medicinal plants) that are spread out in all regions. Darmaji Village is a village in Kopang District, Central Lombok Regency, West Nusa Tenggara, with a very diverse community livelihood, ranging from farmers, breeders, and various types of micro small and medium enterprises (MSMEs). These potentials have not been used to prosper the life of the Darmaji village community, because of the large income inequality for the village community. This community service aims to increase awareness of the Darmaji village community about their potentials, one of which is MSMEs such as processing traditional herbal medicine. This activity is divided into 5 (five) stages, namely (1) the survey phase, this activity is an initial activity to conduct a feasibility study of local potentials and participants who will be involved in the activity, (2) the socialization phase in which the community service team provides relevant information. clearly related to the training program that will be held for prospective training participants, (3) The stage of procurement of tools and goods, the community service team procures the right goods according to the aspects of need, price, efficiency and transparency of use in supporting community service activities, (4) Stage technical training, this activity is a core activity consisting of theoretical and practical activities, and (5) the mentoring stage, namely continuous and systematic assistance carried out to ensure product quality is worthy of being marketed